1992
DOI: 10.1007/bf02285092
|View full text |Cite
|
Sign up to set email alerts
|

Influence of food on the tyramine pressor effect during chronic moclobemide treatment of healthy volunteers

Abstract: An open study was carried out to examine the effect of moclobemide, a new antidepressant reversible inhibitor of MAO-A, on the pressor response induced by oral tyramine added to meals of different lipid and protein composition, and to correlate the blood pressure increase in the tyramine test with that obtained during an exercise test. Eight healthy volunteers of both sexes participated in the study. A tyramine sensitivity and an exercise test were performed beforehand. Subjects were included if, under fasting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

1995
1995
2016
2016

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 16 publications
1
10
0
Order By: Relevance
“…For the present document, outputs from trials in which tyramine was administrated orally accompanying a meal have been taken into consideration, since they are those most closely reproducing the actual situation of food-borne tyramine intake in comparison with pure tyramine in fasting conditions or intravenous injection. Indeed, it has been reported that increasing mainly lipid but also protein content of the meal significantly reduce the tyramine blood pressor response (Audebert et al, 1992). Bioavailability of tyramine when administered with food or as a dietary constituent seems to drastically be reduced and systematic concentrations are reduced by approximately 2-to 3-fold (Patat et al, 1995;Van den Berg et al, 2003;Azzaro et al, 2006).…”
Section: Dose-response Relationshipmentioning
confidence: 99%
See 1 more Smart Citation
“…For the present document, outputs from trials in which tyramine was administrated orally accompanying a meal have been taken into consideration, since they are those most closely reproducing the actual situation of food-borne tyramine intake in comparison with pure tyramine in fasting conditions or intravenous injection. Indeed, it has been reported that increasing mainly lipid but also protein content of the meal significantly reduce the tyramine blood pressor response (Audebert et al, 1992). Bioavailability of tyramine when administered with food or as a dietary constituent seems to drastically be reduced and systematic concentrations are reduced by approximately 2-to 3-fold (Patat et al, 1995;Van den Berg et al, 2003;Azzaro et al, 2006).…”
Section: Dose-response Relationshipmentioning
confidence: 99%
“…Besides inter-and intraindividual variability, the sensitivity to oral tyramine may also vary depending on the diet composition. Lipids but also proteins seem to significantly reduce the tyramine bioavailability (Audebert et al, 1992), though other substances such as alcohol or other biogenic amines can increase tyramine absorption and thus altering/enhancing its vasopressor effect. This uncertainty leads to both underestimation of the adverse vasopressor effect or to an overestimation of the risk.…”
Section: Other Uncertaintiesmentioning
confidence: 99%
“…The study design was based on previous studies (Audebert et al 1992;Patat et al 1995) and is shown in Fig. 1.…”
Section: Methodsmentioning
confidence: 99%
“…According to literature data, the pressor effect peak was expected within 10-30 min following oral tyramine administration (Audebert et al 1992;Patat et al 1995). After determination of the maximal SBP increase (peak) (ΔSBP), the area under the SBP curve (over baseline) (AUC) and the time of latency (t latency ) were calculated.…”
Section: Pressor Effect Analysismentioning
confidence: 99%
See 1 more Smart Citation